Implementasi Nilai – Nilai Literasi Baca Dalam Pembentukan Karakter Peserta Didik Di SMP Negeri 2 Manuju - Muh. Awaluddin Faturrachman; Jumiati Nur; Suardi Suardi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to find out how the implementation of reading literacy values, the learning process in character building carried out by teachers, and the obstacles experienced in the process of implementing reading literacy values in the character building of students at SMP Negeri 2 Manuju.This research uses mixed methods. Mixed methods is combining quantitative methods and qualitative methods in a study or research program, and in a critical review of reality. Mixed research methods are used to obtain a comprehensive analysis of the research problem. Qualitative data collection techniques are in the form of questionnaires, observations, in-depth interviews and documentation. While the quantitative data collection technique is a google form questionnaire. This research was conducted using several stages that have been carried out to achieve success in research.The results showed that: First, the values of reading literacy in the character building of students at SMP Negeri 2 Manuju have been able to be implemented by students where there are five indicators that are implemented, namely, the accuracy of voicing the writing, the reasonableness of memorization, the reasonableness of intonation, fluency, and clarity of voice; Second, the character building process carried out by teachers through reading literacy to students at SMP Negeri 2 Manuju has been implemented by students through the role of teachers with indicators of fond of reading including, reading the Qur'an before starting learning, reading textbooks before starting learning, reading books in the library, reading on the mading in each class and reading books required by the teacher in the form of non-subject books. Third, the obstacles experienced by teachers and students in the process of implementing reading literacy values in the character building of students are the difficulty in understanding the contents of books, behavior and the lack of reading books in the library, so that this can hinder the process of implementing reading literacy values and character building of fond of reading that occurs at the school.